Effects of Peers and Family Members on Smoking Habits in Adolescents: A Meta-Analysis - Florida Betty Apriliyani; Agus Kristiyanto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Nowadays, smoking is one of the biggest public health problems worldwide. It is a major cause of disease and mortality that can be prevented early. One out of 10 deaths worldwide is caused by tobacco use. 40 million people died each year due to tobacco. Adolescents start smoking in response to social effects, imitating the behavior of friends, family members, and others they admire. This meta-analysis study aimed to analyze the effect of peers and family members who smoked on smoking habits in adolescents.Subjects and Method: Meta-analysis was conducted by searching for articles from databases such as PubMed, SpringerLink, Elsevier, Science Direct, and Google Scholar. The keywords were